Advanced aggressive clinical features may be associated with immune dysfunction in patients with HIV-positive Hodgkin lymphoma in the cART era: a multicenter study from China - Liang, Xiping; Wang, Chaoyu; Tang, Yifeng; Xie, Xiaoqing; Wu, Yan; Min, Haiyan; Zhang, Wei; Zhou, Wenwen; Adhikari, Vishnu Prasad; Zhang, Xiaomei; Liu, Yao (Frontiers in Immunology, 2025)
IntroductionCombination antiretroviral therapy (cART)-mediated immune reconstitution can establish a tumor-permissive microenvironment. In addition, compromised immune surveillance may contribute to more aggressive disease phenotypes in HIV patients; however, clinical evidence remains limited.MethodsWe conducted a retrospective analysis of clinical data of newly diagnosed Hodgkin lymphoma (HL) patients from 2014 to 2024 treated at four medical centers in China. The authors conducted clinical and immune function analysis of HIV-positive HL patients with special emphasis on prognosis and immune factors.ResultsIn total, 19 patients were diagnosed as HIV positive. HIV-positive HL patients (HIV-HL) had more advanced stage disease, ECOG-PS, bulky disease, and B symptoms compared to HL patients without HIV (n=130). HIV-positive HL patients had decreased CD4 cell count, CD4/CD8, and GZMB. Lower CD4 count was associated with more bulky disease and B symptoms and higher IL-2R and IL-6 levels in HIV-HL patients. And HIV-HL patients with bulky disease had less GZMB compared to non-bulky disease patients. The enrichment impact of gene alterations on bulky disease demonstrated that PI3K/AKT, thyroid hormone signaling, NF−kappa B signaling pathway, and EBV infection were involved. Immune dysfunction (CD4, CD8, and CD4/CD8), on the other hand, showed no association with survival in both HIV-positive and negative HL patients. There were similar outcomes in patients with and without HIV treated by ABVD chemotherapy.ConclusionHIV-associated Hodgkin lymphoma (HIV-HL) often presents with more aggressive clinical features, although outcomes are similar to those observed in HIV-negative HL patients. Impaired immune function may contribute to an increased tumor burden through multiple mechanisms. However, it was not associated with outcomes. HL treatment approaches might not necessarily require adjustment solely due to HIV status, but additional clinical evidence is needed to support this assertion.